2012
DOI: 10.3390/molecules17067543
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Antiviral Potential of 14-Aryl/Heteroaryl-14H-dibenzo[a,j]xanthenes Using an Efficient Polymer-Supported Catalyst

Abstract: Polyethyleneglycol bound sulfonic acid (PEG-OSO3H), a chlorosulphonic acid-modified polyethylene glycol was successfully used as an efficient and eco-friendly polymeric catalyst in the synthesis of 14-aryl/heteroaryl-14H-dibenzo[a,j]xanthenes obtained from the reaction of 2-naphthol and carbonyl compounds under solvent-free conditions with short reaction times and excellent yields. The biological properties of these synthesized title compounds revealed that compounds 3b, 3c, 3f and 3i showed highly significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…We are interested in the development of various organic transformations under solvent-free conditions [20][21][22] and in exploring the catalytic properties of DBA in two different organic transformations. 15, 19 We found that DBA is a useful precursor for selective chemical transformations.…”
Section: Resultsmentioning
confidence: 99%
“…We are interested in the development of various organic transformations under solvent-free conditions [20][21][22] and in exploring the catalytic properties of DBA in two different organic transformations. 15, 19 We found that DBA is a useful precursor for selective chemical transformations.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our research and interest in the development of novel synthetic methodologies [34], herein we report an efficient method for the synthesis of bisindolylmethanes catalyzed by PEG-OPOCl 2 (Scheme 1). To date, it is the first feasible method for electrophilic substitution at 3-position of indole with various aryl/heteroaryl aldehydes in PEG-OP(O)Cl 2 medium.…”
Section: Resultsmentioning
confidence: 99%
“…A catalyst was prepared according to reported procedure [34]. To a solution of POCl 3 (0.93 mL, 10 mmol) in 20 mL of CH 2 Cl 2 , the mixture of PEG-6000 (30 g, 10 mmol OH) and Et 3 N (1.67 mL, 12 mmol) in 80 mL of CH 2 Cl 2 was added drop-wise at 0–5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Xanthene derivatives are known to exhibit remarkable biological activities like, antibacterial 1,2 , antiviral 3 and CCR1 antagonist 4 and enjoys as a motif for the design and development of pharmacological agents 5 . Xanthene derivative serves as very important and useful starting material in the synthesis of compounds with potential material applications.…”
Section: Introductionmentioning
confidence: 99%